The Exact Linearization and LQR Control of Semiactive Connected Hydropneumatic Suspension System - Xuyang Cao; Linlin Cao; Dianlong Wang (Journal of Control Science and Engineering)
Based on differential geometry theory, the nonlinear system of connected hydropneumatic suspension was transformed to a linear one. What is more, it realized the decoupling and inverter between the control variables and system outputs. With LQR (Linear Quadratic Regulator) control theory, a semiactive system has been developed for connected hydropneumatic suspension in this paper. By AMESim/Simulink cosimulation, the results show that the semiactive connected hydropneumatic suspension decreases the vibration of upper vehicle quickly and reduces the impact acceleration strongly both in displacement and inroll angle. Moreover, the semiactive suspension could increase the suspension dynamic deflection, which would make the system reach balance quickly and keep small vibration amplitude under the effect of disturbance.